A utilização de jogos por professores de geografia na educação básica - Oliveira, Tais Pires de (2018)
This research has as main objective to discuss, in the context of specific didactics, the use of games as a didactic resource by Geography teachers in the teaching-learning process. It seeks to characterize the types of games used by teachers in the classroom, as well as to reflect on the knowledge involved in the process of adaptation, elaboration and use of the game as play material by teachers of Geography. It also intends to identify, considering the perspective of the teachers participating in the research, the potential of games for the development of skills and geographic reasoning in students. To reach the objectives the field research was developed with the teachers of Geography of the Núcleo Regional de Educação of Maringá - NRE / SEED Maringá, Paraná. The methodology adopted to carry out the work privileged the qualitative aspects, without disregarding the quantitative data. The data collection was carried out in two moments: the first consisted of the application of questionnaires, with the participation of fifty-five teachers, and the second moment was developed with semi-structured interviews, which had the participation of four teachers. This information was tabulated and analyzed based on the methodology of content analysis and the bibliography studied. The theoretical reference of this work is based on the understanding of the teaching knowledge, discussed by Tardif (2002), Gauthier et al. (1998), and Shulman (2014), which is based on researchers such as Libâneo (2016), Lopes (2016), Cavalcanti (2002) and Sacramento (2010). (1994), Vial (2015), Grando (1995), Castellar and Vilhena (2011), and to study the relationship between games and teaching, and Oliveira and Lopes (2016). Thus, based on the bibliography consulted and the data collected in the field research, it is possible to infer that the use of games in the teachinglearning process of Geography is recurrent and that, in general, presents satisfactory results. The research evidenced that the games most used by the teachers that participated in the research, according to the form and the content, are the question and answer and assembly games, with the purpose of fixing content, because, they allow, more easily, the adaptation of concepts to the material format. For the participants, the materials used are capable of developing skills and geographic reasoning in students, such as those related to cartographic notions - such as orientation and location - as well as in the exercise with the fundamental concepts of the discipline - such as space and landscape, for example. Beyond geographic concerns, the importance of play in the development of general cognitive abilities and its socializing and regulating power of student group behavior was evidenced. It was also verified that the teaching knowledge involved in the process of using the games, according to the categorization proposed by the authors that give support to this work, without disregarding other knowledge, are: the knowledge of experience, knowledge of the students and their characteristics and the pedagogical knowledge of the content (CPC). The latter, in a special way, reveals the teacher's ability to properly connect the form of the game to its content, articulating geographic knowledge with pedagogical knowledge, to enable students, through games, to reason geographically